ANALISIS PERHITUNGAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN SERTA KONTRIBUSINYA TERHADAP PAD DI KABUPATEN MINAHASA (TAHUN 2013-2017) - Luntungan, Gratia Tita; Manossoh, Hendrik; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Tax is the main source of a country that is used by the government to finance expenses in order to achieve prosperity and prosperity. Local taxes and levies are a source of regional original income (PAD), one of the potential taxes, namely the tax on non-metallic minerals and rocks. This study aims to see how the tax on non-metallic minerals and rocks in increasing tax revenues and to determine the contribution of non-metallic and coal mining taxes to regional original income (PAD). The research method used is a qualitative descriptive method. The results of this study note that the average contribution of local taxes to PAD over a period of 5 years is 0.268%, which means that the contribution of local taxes is very lacking and for calculations obtained by the Office of BPP-Retda in Minahasa District through the tax base Predetermined nonmetallic minerals and rocks.